INTERDISCIPLINARY CONSENUS ON THE MANAGEMENT OF IIH IN THE UK. Issue 12 (15th November 2016) - Hassan-Smith, Ghaniah; Mollan, Susan; Davies, Brendan; Shaw, Simon; Chavda, Bhawisha Swarupsinh; Krishnan, Anita; Mallucci, Conor; Silver, Nicholas; Wakerley, Benjamin; Sinclair, Alexandra
Abstract : Management of Idiopathic Intracranial Hypertension (IIH) is not standardised. A multidisciplinary Special Interest Group (SIG) was established to develop a uniform investigation and treatment strategy according to disease severity based on current literature and expert consensus. Methods: A systematic literature review of "IIH";"Benign IH" and "pseudotumour cerebri" was followed by a SIG meeting, to identify the population, interventions, controls and outcomes (PICO) questions. Discrepant views were reflected in a questionnaire disseminated though a modified Delphi approach to district general and tertiary hospital interdisciplinary specialists. Results: 44/66 questionnaires were returned. 51% would image (CT/MRI) patients with definite papilloedema <24 hrs and 40% would image between 24–48 hrs. In these patients 84% would then proceed to venography (50:50, MRV:CTV), conducted within 48 hrs in 74% respondents.79% never diagnosed IIH in those with a lumbar puncture pressure <25 cm CSF. Referral for neurosurgical intervention was predominantly for visual deterioration (83%) with only 2% referring exclusively for headache management. Neurosurgical procedures varied: 48% ventriculoperitoneal shunting, 33% lumboperitoneal shunting, 5% optic nerve sheath fenestration, 14% other and 0% venous stenting. A consensus on follow-up times, according to papilloedema severity and visual function (perimetry), was obtained. Conclusions: Evidence for IIH management is minimal. Consensus on many aspects of management was demonstrated which will help establish a practical guideline.